2008
DOI: 10.1508/cytologia.73.269
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Pairing and Chiasma Formation in Some Olive (Olea europaea L.) Cultivars of Iran

Abstract: Summary Cytogenetic characteristics of 11 olive cultivars were studied considering their chromosome pairing and segregation. The cultivars studied possessed 2nϭ4xϭ46 chromosome number and formed only bivalents in metaphase of meiosis-I. The cultivars differed significantly in their chiasma frequency and distribution as well as chromosome pairing indicating partly their genetic distinctness. Meiotic abnormalities including laggard chromosomes and chromosome stickiness occurred in the cultivars studied. B-chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
4
10
0
Order By: Relevance
“…Young flower buds were collected from 10 randomly selected plants of each species/population and fixed in glacial acetic acid : ethanol (1 : 3) for 24 h. Flower buds were washed and preserved in 70% ethanol at 4°C until used (Sheidai et al 2008). Cytological preparations used squash technique and 2% aceto-orcein.…”
Section: Cytological Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Young flower buds were collected from 10 randomly selected plants of each species/population and fixed in glacial acetic acid : ethanol (1 : 3) for 24 h. Flower buds were washed and preserved in 70% ethanol at 4°C until used (Sheidai et al 2008). Cytological preparations used squash technique and 2% aceto-orcein.…”
Section: Cytological Studymentioning
confidence: 99%
“…For grouping of the species a combined data set was produced from meiotic data obtained in this study and karyotype data reported before (Sheidai and Rashid 2007). Since the species studied differed in their chromosome number, relative cytological data were used, for this purpose, mean of ring and rod bivalents per cell, mean of univalents per cell and total chiasmata per bivalent were used (Sheidai et al 2008).…”
Section: Cytological Studymentioning
confidence: 99%
See 3 more Smart Citations